Global Warming Impacts Study of Tofu Products in Mampang Prapatan Small and Medium Enterprises with Life Cycle Assessment Methods - Bayu Sukmana; Isti Surjandari; Muryanto .; Arief A. R. Setiawan; Edi Iswanto Wiloso (Indonesian Journal of Life Cycle Assessment and Sustainability, 2019)
Firstly global warming issue caused by greenhouse gas emissions (CO2) which comes from human activities. Along with increasing of daily need, that humans of activities food produce is also increase, include of tofu. Tofu is a traditional Indonesian specialty made from soybeans and used as a side dish. The purpose of this study was to determine the impact of global warming from tofu products on Mampang Prapatan's Small Tofu and Medium Enterprises. The method used in this study is the Life Cycle Assessment (LCA) method with the help of Simapro 8.4 software with a 1 kg tofu functional unit. The data collected in this study is the average data of tofu production for 3 months, namely January - March 2018. The LCA data in this study include the process of soybean cultivation, transportation processes for shipping soybeans, water, fuel wood, and electricity use. The limitations of this study are from cradle (soybean cultivation) to gate (tofu products).The results showed that UKM Mampang Prapatan has the potential impact of global warming with a value of 3.84 kg CO2-eq, while the value of global warming in the production process knows the scenario of wastewater treatment and the use of Liquefied Petroleum Gas (LPG) as fuel for boiling pulp 4.49 kg CO2-eq soybeans. Based on the results of this study, greenhouse gas (CO2) emissions are issued; the intervention that can be done is to optimize the use of raw materials for production to reduce the impact of CO2-eq kg global warming.